2018
DOI: 10.2196/jmir.9160
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Online Consumer Ratings of Health Care Providers Across Medical, Surgical, and Allied Health Specialties: Observational Study of 212,933 Providers

Abstract: BackgroundHealth care consumers are increasingly using online ratings to select providers, but differences in the distribution of scores across specialties and skew of the data have the potential to mislead consumers about the interpretation of ratings.ObjectiveThe objective of our study was to determine whether distributions of consumer ratings differ across specialties and to provide specialty-specific data to assist consumers and clinicians in interpreting ratings.MethodsWe sampled 212,933 health care provi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Furthermore, it is necessary to verify the validity of the score by applying it to patients independent from the derivation group [ 9 ]. Discrimination was measured by AUC [ 10 ]. It is generally defined as useful if AUC is >0.7 and is defined as excellent if AUC is between 0.8–0.9 considering the diagnostic accuracy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is necessary to verify the validity of the score by applying it to patients independent from the derivation group [ 9 ]. Discrimination was measured by AUC [ 10 ]. It is generally defined as useful if AUC is >0.7 and is defined as excellent if AUC is between 0.8–0.9 considering the diagnostic accuracy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, McGrath and colleagues recently reported that patients tend to give more favorable reviews to doctors listed on Castle Connolly Medical's "America's Top Doctors, " a peer-reviewed title that carries a sense of prestige or, at the very least, esteem (20). Moreover, surgical subspecialties often associated with higher incomes tend to receive higher ratings than their generalist counterparts (21,22). In our cohort we did not replicate these findings, as there was a small negative correlation between income and ratings in the surgical cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The trust level task is designed through the average rating value (ARV), which is used to calculate the average trust value given by the patient to their physician. The ARVs were generated based on the idea of Marsh [ 41 ] and Daskivich [ 56 ] to identify the trustworthiness level of a physician or patient with independent values. The trustworthiness level and independent value of a physician denoted by ARV are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The patient allows viewing the trust value and trust level of physicians. A physician’s trust value is based on the average of the trustworthiness indicators [ 28 ] and the ARV as the rating trust level [ 41 , 56 ]. The trust level of a physician is then identified by the trust value.…”
Section: Methodsmentioning
confidence: 99%